Circulating Epstein–Barr virus DNA level post induction chemotherapy contributes to prognostication in advanced-stage nasopharyngeal carcinoma. (July 2021) - Chen, Fo-Ping; Luo, Ying-Shan; Chen, Kai; Li, Jun-Yun; Huo, Lan-Qing; Shi, Liu; Ou-Yang, Yi; Cao, Xin-Ping
Abstract: Background: To investigate the value of post-induction chemotherapy (IC) cell-free Epstein–Barr virus DNA (cfEBV DNApostIC ) for prognostication in locally advanced nasopharyngeal carcinoma (LA-NPC). Methods: A total of 910 histologically proven LA-NPC undergoing radical IC + concurrent chemo-radiotherapy (CCRT) or targeted radiotherapy (CTRT) or both (CTCRT) were involved. The concentration of cfEBV DNA was measured by quantitative polymerase chain reaction pre-IC (cfEBV DNApreIC ) and at IC completion. CfEBV DNApostIC was classified as undetectable (0 copy/ml) and detectable (>0 copy/ml). Recursive partitioning analysis (RPA) with respect to the overall survival (OS) was applied to construct a risk stratification system incorporating cfEBV DNApostIC and critical risk factors. Results: We observed that 660 (72.5%) and 250 (27.5%) patients had cfEBV DNApostIC undetectable and detectable respectively. CfEBV DNApostIC positive was associated with a significant inferior 5-year OS (76.2% versus 85.9%), metastasis-free survival (DMFS, 71.7% versus 86.4%) and disease-free survival (DFS, 57.7% versus 80.1%) than cfEBV DNApostIC negative ( P  < 0.001 for all). Additionally, cfEBV DNApostIC was independently significant for OS (hazard ratio [HR] 1.90, 95% CI 1.40–2.59), DMFS (1.99, 1.45–2.71) and DFS (2.38, 1.86–3.06) in multivariate analyses ( P  < 0.001 for all). RPA modelling yielded three distinct risk groups: low-risk (N0-1 and undetectable cfEBV DNApostIC or N2-3 and pre-treatment cfEBV DNA [cfEBV DNApreIC ] <7000), median-risk (N0-1 and detectable cfEBV DNApostIC or N2-3 and cfEBV DNApreIC ≥7000 with undetectable cfEBV DNApostIC ) and high-risk (N2-3 and cfEBV DNApreIC ≥7000 with detectable cfEBV DNApostIC ), with 5-year OS of 88.1%, 79.2% and 66.9%, respectively. Our risk stratification outperformed TNM classification for predicting death (AUC, 0.631 versus 0.562; P  = 0.012) and distant metastasis (0.659 versus 0.562; P  = 0.004). Conclusions: CfEBV DNApostIC represents an effective indicator of prognostication in LA-NPC. We developed a risk classification system that provides improved OS prediction over the current staging system by combining cfEBV DNApostIC, cfEBV DNApreIC and N-stage classification in LA-NPC. Highlights: CfEBV DNApostIC positive was independently risk for metastasis/death in LA-NPC. We constructed a cfEBV DNApostIC -based risk classification system in LA-NPC. Risk stratification is superior to TNM schema in predicting death and metastasis.